Homework Help Question & Answers

How do you solve #5(-3x-2)-(x-3) = -4(4x+5)+13#?

How do you solve #5(-3x-2)-(x-3) = -4(4x+5)+13#?
0 0
Add a comment
Answer #1

#x# has any value.

Explanation:

Remove the brackets first using the distributive law.

#5(-3x-2) -(x-3) = -4(4x+5)+13#

#-15x-10-x+3 = -16x-20+13#

#-16x -7 = -16x-7" "larr# both sides are identical.

#-16x+16x = -7+7" "larr# this leads to

#0=0" "larr# true, but there is no #x# to solve for.

This is an identity which means that it will be true for any value of #x#

answered by: EZ as pi
Add a comment
Know the answer?
Add Answer to:
How do you solve #5(-3x-2)-(x-3) = -4(4x+5)+13#?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coin

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for? Ask your own homework help question. Our experts will answer your question WITHIN MINUTES for Free.
Free Homework Help App
Download From Google Play
Scan Your Homework
to Get Instant Free Answers
Need Online Homework Help?
Ask a Question
Get Answers For Free
Most questions answered within 3 hours.